2010
DOI: 10.1007/s11829-010-9109-0
|View full text |Cite
|
Sign up to set email alerts
|

What weta want: colour preferences of a frugivorous insect

Abstract: Plants use colours as signals to attract mutualists and repel antagonists. Fleshy-fruits are often conspicuously coloured to signal different types of information including fruit maturity and spatial location. Previous work on fruit colour selection focus on large diurnal vertebrates, yet fruit colours are perceived differently by frugivores with different types of visual systems. Here, we tested whether a nocturnal, frugivorous, seed-dispersing insect selects fruits based on their pigmentation and whether dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Given the ecological similarities between weta and the small mammals that occupy similar niches in other parts of the world, they are sometimes referred to as New Zealand's invertebrate mice (Gibbs, ). A detailed investigation has revealed that weta do indeed act as seed dispersal agents, as mice do (Duthie et al ., ; Fadzly & Burns, ). While weta might be exceptional endozoochorous seed dispersal insects, it is possible that endozoochory could occur whenever seeds can be swallowed whole and are resilient enough to remain intact after passage through their gut (De Vega et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…Given the ecological similarities between weta and the small mammals that occupy similar niches in other parts of the world, they are sometimes referred to as New Zealand's invertebrate mice (Gibbs, ). A detailed investigation has revealed that weta do indeed act as seed dispersal agents, as mice do (Duthie et al ., ; Fadzly & Burns, ). While weta might be exceptional endozoochorous seed dispersal insects, it is possible that endozoochory could occur whenever seeds can be swallowed whole and are resilient enough to remain intact after passage through their gut (De Vega et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…Typically, fleshy fruits are divided into a ‘bird’ syndrome of small fruits with bright or contrastive colours such as red, black and blue, and a ‘mammal’ syndrome of larger fruits with dull colours such as green, brown or yellow, often with an odour and/or protective husk (Janson, ; van der Pijl, ). A variety of complexities in these syndromes have been noted (e.g., Fadzly & Burns, ; Lord & Marshall, ), and doubt has been cast on the extent to which seed dispersers actually select for fruit traits. Many animals consume a broad range of fruit colours, including fruits displaying traits belonging to all syndromes (Fischer & Chapman, ; Kitamura et al, ; Poulsen, Clark, Connor, & Smith, ; van der Pijl, ), and preferences can vary even among individual animals and over time (Willson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, most insects lack visual receptors for the colour red (Willson & Whelan ), and the fleshy fruits of plants endemic to New Zealand are often white or translucent and are often displayed in the inner recesses of plant canopies (Burns ). These unusual characteristics of New Zealand fruits have been attributed to co‐evolutionary adaptations that facilitate seed dispersal by weta (Burns ; Fadzly & Burns ). It is intriguing that heterotrophic plants that utilise camel crickets for seed dispersal generally also possess white or translucent fruits, especially because it suggests the existence of an orthopteran‐mediated seed dispersal syndrome.…”
Section: Discussionmentioning
confidence: 99%